Effects of Unsuppressed Endogenous Insulin on Pharmacokinetics and/or Pharmacodynamics of Study Insulin in the Healthy: A Retrospective Study. Issue 8 (5th April 2022) - Liu, Hui; Yu, Hongling; Sun, Lisi; Qiao, Jingtao; Li, Jiaqi; Tan, Huiwen; Yu, Yerong
Abstract: C‐peptide, a marker of endogenous insulin, should be consistently inhibited during euglycemic clamping, while an elevated postdosing C‐peptide (CPpostdosing ) is not an occasional phenomenon. This was a retrospective study that included 33 men who underwent a manual euglycemic clamp with a subcutaneous injection of insulin aspart (IAsp) aiming to describe the effects of insufficient suppression of endogenous insulin on estimates of the pharmacokinetics and pharmacodynamics of injected insulin. The time profiles of whole blood glucose, human insulin, glucose infusion rate (GIR), and C‐peptide were recorded. The subjects were divided into 2 groups at a ratio of 2:1: group A ([CPpostdosing ]max >baseline CP [CPbaseline ]), group B ([CPpostdosing ]max ≤ CPbaseline ). The endogenous insulin was approximately equal to the measured value of human insulin or calculated from the C‐peptide. The basal glucose, CPbaseline, basal human insulin, homeostatic model assessment of insulin resistance, IAsp dose, and demographic statistics were all comparable between the 2 groups except the "clamped" glucose. The average clamped glucose was 99.7% (group A) and 94.9% (group B) of baseline. After correction for clamped glucose, GIR area under the concentration‐time curve from time 0 to 8 hours was higher in group A ( P < .05) under comparable IAsp exposure. Endogenous insulin area under the concentration‐time curve from time 0 to 8 hours calculated from C‐peptide was different from that measured from human insulin in group A ( P < .05), whereas no statistical difference between these measures was observed in group B. Hence, blood glucose should be controlled below the baseline to ensure the inhibition of endogenous insulin. Unsuppressed endogenous insulin may contribute to observed GIR, and the endogenous insulin–corrected pharmacokinetics estimated by C‐peptide may be inaccurate with insufficient endogenous insulin suppression.